Literasi Kesehatan terhadap Kepatuhan Minum Obat pada Pasien Hipertensi: Literatur Review - Alifariki, La Ode (NHM PRESS, 2024)
Hypertension is one of the most prevalent chronic diseases worldwide, and its management highly depends on patients' adherence to medication. One of the factors influencing medication adherence is health literacy, which encompasses an individual's ability to understand and use health-related information in decision-making. This study aims to examine the relationship between health literacy and medication adherence in hypertensive patients through a literature review. Based on 10 relevant articles, it was found that higher health literacy is associated with better medication adherence because patients who have a good understanding of their disease and treatment are more likely to adhere to the prescribed regimen. Conversely, low health literacy may lead to misunderstandings of medication instructions, potentially decreasing adherence. Various factors, such as communication methods used by healthcare providers, social support, and health education programs, have proven effective in improving patients' health literacy. The findings of this review indicate that enhancing health literacy through clearer education and appropriate support is crucial for improving medication adherence and reducing the risk of hypertension-related complications. Therefore, a more holistic and individualized approach is needed in the management of hypertension to achieve optimal treatment outcomes